Bio-mediated generation of food flavors – Towards sustainable flavor production inspired by nature. (August 2018) - Bel-Rhlid, Rachid; Berger, Ralf Günter; Blank, Imre
Abstract: Background: The consumers' trend toward naturalness and "clean-label" products advocates the development of "bio-mediated" tools including new processes for the generation of flavors. Today, many fundamental studies demonstrate the feasibility of producing individual flavor compounds or more complex flavoring preparations by fermentation or by enzymatic reactions. However, to turn research into industrial applications, the processes have to be simplified and optimized by combining chemistry, biology and process engineering know-how. Scope and approach: This review summarises recent basic research and development on cell and enzyme based formation of volatile flavors with focus on smart combinations of biocatalytic and thermal steps to enrich the natural flavor profile of foods. Ideally, targeted bioconversion of specific raw materials and ingredients will release flavor precursors required to generate the desired flavor profile by appropriate thermal processing. Key findings and conclusions: The combination of fermentation or enzymatic treatment of raw materials with heat-induced food processes (e.g. drying, extrusion, roasting) represent an elegant approach in industrial food processing to generate flavors under mild conditions. This requires a good control of fermentation or enzymatic reaction steps to produce suitable substrates at the optimal concentrations adapted to the thermal processes. Using traditional cooking and minimal processing conditions (nature-inspired strategies) has become an attractive approach to generate authentic flavor profiles resonating with consumers' demand for more naturalness. Highlights: Combined bio-catalytic and thermal steps can enrich the natural flavor profile of foods. The return to fermentation offers a convenient option to food flavor generation. Synthetic biology is a valuable approach to produce natural flavors. Mild processing of foods plays a key role in flavor quality and intensity. Cost, robustness, yield and regulatory are the main hurdles to the application of enzymes in food flavors generation.